2019
DOI: 10.1002/jcph.1452
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metformin Use With End‐Stage Renal Disease in Patients With Type 2 Diabetes Mellitus: A Nationwide Cohort Study Under the Pay‐for‐Performance Program

Abstract: Animal studies have demonstrated that metformin exerts a renoprotective effect. Human studies of patients with diabetes mellitus (DM) regarding the association of metformin use with end‐stage renal disease (ESRD) are lacking. Patients with type 2 DM and without a history of kidney disease who were enrolled under the pay‐for‐performance program of the National Health Insurance in Taiwan were identified. Those who received ≥90 cumulative defined daily doses of metformin within 1 year were selected (metformin use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The aim of that study was to assess the impact of metformin on the development of end-stage kidney disease and CKD. The findings indicate that among metformin users vs. non-users the risk of the end-stage kidney disease and CKD development was 22% and 25% higher, respectively [234].…”
Section: Nephroprotectionmentioning
confidence: 95%
“…The aim of that study was to assess the impact of metformin on the development of end-stage kidney disease and CKD. The findings indicate that among metformin users vs. non-users the risk of the end-stage kidney disease and CKD development was 22% and 25% higher, respectively [234].…”
Section: Nephroprotectionmentioning
confidence: 95%
“…These findings may have been driven mainly by the effect of metformin on mortality, as the analysis was neutral for ESRD as an individual outcome. A study of 24 158 matched pairs of metformin users and non‐users from the Taiwan National Health Insurance database suggested a small but significant increase in the risk of ESRD with metformin . Interestingly, in a recent subgroup analysis of the EMPA‐REG Outcome trial, it was suggested that renoprotection with empagliflozin might be attenuated by background metformin therapy on the basis that there was a non‐significant trend ( P for interaction = 0.07) towards higher hazard ratios for nephropathy events with concomitant metformin therapy (0.68 [95% CI 0.58 to 0.79]) compared with no metformin therapy (0.47 [95% CI 0.37 to 0.59]) .…”
Section: Metformin In Chronic Kidney Diseasementioning
confidence: 99%
“…Based on a study by Richy et al, the administration of metformin showed no difference in the prevalence of lactic acidosis in patients with T2D who had normal, mild, moderate, or severe renal dysfunction (44). Recently, a retrospective observational cohort study by Lee et al, reported that metformin users probably develop ESRD and CKD more than non-metformin users (45). While Lalau et al reported no adverse effects for the use of metformin in different CKD stages (46).…”
Section: Metformin Chronic Kidney Disease and Lactic Acidosismentioning
confidence: 99%